The Role of Parents in Children's Learning Outcomes and Character (Case Study in Harapan Ummat Integrated Islamic Elementary School Ngawi) - Setyowati, Ririn (Civiliza Publishing, Indonesia., 2025)
A child's initial introduction to society is through their parents. The family, as a child's first educational environment, is critical in establishing the conditions required to advance through the stages of individual development reinforced in the school setting. As a result, further research on parents' roles in their children's education is required. This study aims to (1) analyze the role of parents in children's learning outcomes; (2) analyzing the role of parents in the character of children; (3) describe the annual activities of Harapan Ummat Integrated Islamic Elementary School in developing parents' knowledge of children. This study used a qualitative descriptive method. Data sources were obtained from 84 students and three teachers at Harapan Ummat Integrated Islamic Elementary School. Data collection was conducted through interviews, observation, and documentation. Data were analyzed using triangulation techniques. The results of the study indicate that parents are the main driving factor in the development of children's intelligence and character. Annual activities held at Harapan Ummat Integrated Islamic Elementary School include parenting seminars, family gatherings, and regular meetings between parents, which are appropriate strategies for establishing interactive communication to develop learning outcomes and instill character in students.